Developing a self-help career resource for international Chinese doctoral students in Australia. (October 2019) - Lee, Myra CY; McMahon, Mary; Watson, Mark
International Chinese doctoral students to Australia are a growing demographic but little research has examined support for their career decisions. The Journey to the West Guide has been developed as a self-help career resource to support these students' navigation of international career transitions. Based on interview data from this cohort, a prototype Guide was developed, and feedback was sought from potential users to refine the Guide. This article proposes a four-step process (i.e., Conception, Design, Testing, and Guided Intervention ) for developing career resources derived from literature concerning the development of career assessment and intervention. This process served as a framework to analyse the feedback with a view to refining the prototype. Practical implications regarding self-help career resources are discussed.